Interim Monitoring Report of Beaked Redfish (Sebastes mentella and S. fasciatus) in NAFO Division 3M - Ávila de Melo, A.; Saborido-Rey, Fran; Alpoim, R. (Northwest Atlantic Fisheries Organization, 2004)
11 páginas, 3 figuras, 3 tablas. The present report updates for 2003 the most relevant commercial and survey data used in the assessment of the Division 3M beaked redfish stock. From the data presented there are no signs of a change in the status of the 3M beaked redfish stock from 2002 to 2003. This assessment is part of a EU research project supported by the European Commission (DG XIV, Program for the collection of data in fisheries sector), IPIMAR, CSIC, IEO and AZTI. Peer reviewed